De novo sekvenování genomu Crenicichla semifasciata technologií Oxford Nanopore - Mikešová, Adéla (Jihočeská univerzita, 2022)
The submitted bachelor thesis deals with de novo sequencing of genome of the cichlid species Crenicichla semifasciata on the Oxford Nanopore platform and its assembly with the Flye algorithm. The study further investigates the influence of sequencing depth on the BUSCO completeness assessment and N50 metrics of the obtained assembly.
The De Novo Genome Sequencing of Crenicichla semifasciata using Oxford Nanopore Technology
Keywords: MinION; kompletnost BUSCO; adaptivní radiace; dlouhé sekvence; MinION; BUSCO completness; adaptive radiation; long reads